Bending strength and design methods of the 6082-T6 aluminum alloy beams with circular hollow sections. (August 2020) - Zhao, Yuanzheng; Zhai, Ximei
Graphical abstract: Abstract: Circular hollow section (CHS) specimens are widely employed in long-span space structures, truss structures, and bridge structures; however, only a few experimental and numerical investigations on CHS aluminum alloy beams have been conducted in China. This paper presents a detailed experimental investigation on CHS beams made of 6082-T6 aluminum alloys. The effects of length and section slenderness on the ultimate strength and buckling behaviour were investigated. Seventeen extruded CHS specimens were subjected to four-point bending tests, with the diameter-to-thickness ratio ( D / t ) ranging from 16.4 to 29.1. The failure modes observed included overall buckling and the coupling of local and overall buckling. The initial geometric imperfections were measured prior to the bending tests. Subsequently, fine finite-element (FE) models were developed using the nonlinear analysis program ABAQUS and validated against the experimental results. An extensive parametric study involving 600 numerical results was performed to evaluate the effects of D / t, the section dimensions, and the slenderness ratio on the mechanical responses and bending strength of the CHS beams. The test results, together with the obtained FE analysis results, were utilised to assess the accuracy of the bending-strength provisions in the current design codes GB 50429 (China), Eurocode 9 (Europe), and AA-2015 (America), as well as optional design approaches, i.e. the direct strength method (DSM) and continuous strength method (CSM). The results indicated that all five design provisions provided conservative predictions of the ultimate moment capacities; the predicted results of DSM and CSM were more accurate than the three design specifications. The reliability levels of the bending-strength provisions were confirmed and compared using statistical parameters from the corresponding specifications.